Minimum Inhibitory Concentration and Minimum Bactericidal Concentration of Areca Nut Ethanolic Extract Against Streptococcus mutans and Escherichia coli using Broth Dilution Method - Adrianz Mario Tethool; Claudius Hendraman B. Tobi; Mustika Endah Pratiwi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Antimicrobial Resistance (AMR) is the global problems that continously develop. Two bacteria that are the most pathogenic are Streptococcus mutans (S. mutans) and Escherichia coli (E. coli). The AMR requires new strategies to address this health problem, including the development of new drugs from natural products. Through this study, we aimed to discovering the antibacterial activity of Areca Nuts against S. mutans and E. coli as potential new antibiotics from natural products. The study begin with extration process, then continued with characterization of extract, bacteria identification, and determination of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). This study obtained the yield percentage of extract was qualified the standard reference (28.95%). The characterization of extract showed the extract meet the qualification based on loss on drying, water content, ash content and total count plate parameters. The MIC values of Areca Nut ethanolic extract against S. mutans is 250 ppm and against E. coli is 62.5 ppm. The MBC values of Areca Nut ethanolic extract against S. mutans is 500 ppm and against E. coli is 62.5 ppm. The result show the ethanol extract of areca nut seeds has antibacterial activity with bactericidal properties, where the ethanol extract of areca nut seeds is more effective against E. coli bacteria than S. mutans bacteria.